Community-Based Ecological Empowerment through Customary Law: A Philosophy of Law Perspective from the Selorejo Indigenous Community - Fitri Ariska; Abd. Mu'id Aris Shofa; Mifdal Zusron Alfaqi; Laksamana Prammana Agung (GUYUB: Journal of Community Engagement, 2026)
The ecological crisis caused by massive land conversion over the last two decades has contributed to environmental degradation in the Greater Malang area. Data from the Indonesian Forum for the Environment (WALHI) in 2021 recorded the loss of 348 hectares of primary forest, indicating the erosion of the region’s ecological integrity. This community-based empowerment initiative aimed to strengthen ecological awareness through the documentation and dissemination of customary ecological knowledge in the Selorejo Indigenous Community. The program was implemented through community discussions, field documentation, and the production of a documentary film highlighting customary law practices and local wisdom in environmental conservation. Data were collected through observation, interviews, discussions with community members, and documentation of customary conservation practices. The results show that the documentary process facilitated the preservation of local ecological knowledge and strengthened community reflection on the importance of forest protection, water resource conservation, and environmental stewardship. Customary practices, including collective forest protection, traditional rituals, community deliberation, and shared environmental responsibilities, encourage active community participation in environmental governance. Furthermore, the documentary film serves as an educational medium for disseminating ecological values and customary environmental norms to broader audiences. These findings demonstrate that customary law functions not only as a socially legitimate system of norms but also as a community-based mechanism for ecological empowerment, strengthening ecological legal awareness and supporting sustainable environmental conservation.